Participation of Local Community in Development Costal Ecotourism of South Cingkuak Island, West Sumatra Province - Riadi, Matgus; Yoswaty, Dessy; Mulyadi, Aras (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in January 2013 in South Painan Nagari Cingkuak Island District IV Jurai South Coastal District of West Sumatra Province. This study aims to determine the potential of marine ecotourism of Cingkuak Island and determine the level of community participation, the government and other stakeholders in the development of marine ecotourism. The method used in this study is a survey method. Data taken and observed consist of primary and secondary data. The sample selection of the interview conducted by using purposive sampling method.Cingkuak island has potential for marine tourism and a significant opportunity to develop a marine ecotourism. Ecosystems contained island ecosystem cingkuak like coral reefs, seagrass, mangrove and wealth of flora and fauna. Things that support marine ecotourism in the Cingkuak Island parameter water quality, geomorphology, climate, and adequate infrastructure. Community participation can be seen coming from the tour players. Not only from the local community but also the participation of domestic and foreign tourists.Keywords: Potential of Marine Ecotourism, Community Participation, Cingkuak Island